Impact of renewable carbon on the properties of composites made by using three types of polymers having different polarity. Issue 10 (15th October 2020) - Rodriguez‐Uribe, Arturo; Snowdon, Michael R.; Abdelwahab, Mohamed A.; Codou, Amandine; Misra, Manjusri; Mohanty, Amar K.
Abstract: Pine wood derived biocarbon (BioC) is investigated as a renewable alternative to carbon black (CB) for plastics and composites applications. Three different polymers with different polarity were used to prepare the composites: polypropylene (PP), polylactic acid (PLA), and polyamide 6 (PA6). Comparatively, CB had a nodule size of 300 nm and surface area of 8 m 2 /g, whereas BioC showed an average particle size of 950 nm and surface area of 260 m 2 /g, respectively. CB, in the composites, was found in large aggregations in the flow direction (FD), while BioC particles showed a better dispersion. Aggregation of CB affected mostly the mechanical strength of the composites. Furthermore, it was found that the overall performance of composites was influenced more by the polarity of the phases, rather than the particle size or the surface area of the fillers. Even when the polarity of the particles had an expected trend (PA6 > PLA > PP with BioC > CB), the work of cohesion obtained for the composites was PA6‐BioC > PP‐BioC > PLA‐BioC, showing, in particular, that the chain‐to‐chain intermolecular forces in neat PLA are stronger as compared to those developed by the particle‐matrix interactions. Abstract :